(untitled) (Reflection and Critique Law Magazine, 2024)
This article analyzes the constitutionality and the impacts of changes in Law no. 13,964 / 19 in the Criminal Procedure Code caused by the creation of the Guarantee Judge. Based on this, it is investigated how this criminal procedural alteration can influence the construction of an effectively accusatory procedural model in Brazil, since the aforementioned figure aims to create conditions that allow the magistrate responsible for the judgment to move further away from the case, preliminary investigation and preserving the impartiality. Thus, through the bibliographic analysis and the conflicting understandings, the (un) constitutionality of the measure is explored, as well as its effect on the construction of the accusatory model.